Effects of selenium on proliferation, interleukin-2 production and selenoprotein mRNA expression of normal and dexamethasone-treated porcine splenocytes. (February 2015) - Zhuang, Tenghan; Xu, Haibin; Hao, Shu; Ren, Fei; Chen, Xingxiang; Pan, Cuiling; Huang, Kehe
Highlights: The immune state modulation of Se is stronger in DEX-treated splenocytes than normal splenocytes. The results explain the controversy of varying reports on the modulation of the immune state of splenocytes by Se. Abstract: Porcine splenocytes were isolated in vitro, treated with different levels of dexamethasone (DEX), and stimulated by concanavalin A. Further, the normal (non-DEX-supplemented) or DEX-treated (0.01 µmol/L) splenocytes were incubated with 0, 0.5, 2, and 5 µmol/L Na2 SeO3 . The splenocyte proliferation, IL-2 production, intracellular glutathione peroxidase 1 (GPx1) mRNA level and activity and thioredoxin reductase 1 mRNA level were measured. The results showed that addition of 0.5 or 2 µmol/L Na2 SeO3 significantly promoted normal and DEX-treated splenocyte proliferation, IL-2 production and GPx1 mRNA expression and activity ( P  < 0.05), respectively. The maximum effect was observed in DEX-treated splenocytes with 0.5 µmol/L Na2 SeO3 . Thus, our results show that the immune state modulation of Se is stronger in DEX-treated splenocytes than normal splenocytes. The mechanism underlying this effect may be increased in GPx1 expression induced by Se. Our results explain the controversy of varying reports on the immune state modulation induced by Se.